The Effect of Three Different Types of Corrective Feedback on Students’ Academic Writing in Higher Education - Dewi, Finita; Jati, Anuncius Gumawang (Beyond Words, 2017)
This present study compared three different modes of corrective feedback – peer corrective feedback, teacher-written corrective feedback and video-based corrective feedback – to investigate which mode was more beneficial for students’ academic writing skill. The participants were 120 first semester university students taking academic writing course. An Analysis of Variance (ANOVA) was performed to determine the relationship between students’ academic writing performance and the mode of corrective feedback they experienced with. In addition, a post hoc Tukey’s HSD test was conducted to explore the differences among the corrective feedback given to the students. The result shows that corrective feedbacks provided by teachers – written and video-based – were statistically significant in assisting students’ academic writing performance. In addition, it is also revealed that teacher-written feedback is still regarded as the most beneficial mode of feedback for students’ writing.